Porcelain a memoir - Moby Musiker 1965- (Faber and Faber, 2016)
From Moby, one of the most interesting and iconic musicians of our time, comes a piercingly tender, funny, and harrowing account of the path from suburban poverty and alienation to a life of beauty, squalor, and unlikely success. It's about making it, losing it, loving it, and hating it. It's about finding your people, your place, thinking you've lost them both, and then, somehow, when you think it's over, from a place of well-earned despair, creating a masterpiece. ...